Analysis Of The Work Motivation Factors On An Employee Performance - Laila Irawati; Khaeruman; Yuary Farradia (International Journal of Educational Research & Social Sciences, 2021)
The importance of motivation is because motivation is the cause and supporter of human behavior so that they are willing to work hard and enthusiastically to achieve optimal results. Motivation is increasingly important in an organization or company because the leader distributes work to his staff to be done well and integrated to achieve the desired goals. The method used in this study refers to the " associative or relationship research method, namely research methods that aim to determine the relationship between two or more variables. The source of data in this study is primary data, namely from distributing questionnaires directly to respondents who became the research sample, namely employees of telecommunications companies in Indonesia, totaling 30 people. To find out what factors dominantly affect work motivation and employee performance. The analysis technique or data processing uses frequency distribution and comparison of the average number of each motivational factor to determine what factors are the most dominant on employee motivation and performance. Based on the results of research that has been carried out through questionnaires and calculated based on the average value of each factor, it is obtained that the dominant factor of work motivation and performance is a harmonious relationship between fellow staff in the company.